Modeling stiffness of connections and non-structural elements for dynamic response of taller glulam timber frame buildings. (15th June 2022) - Tulebekova, Saule; Malo, Kjell Arne; Rønnquist, Anders; Nåvik, Petter
Abstract: Currently, there is limited knowledge of the dynamic response of taller glue laminated (glulam) timber buildings due to ambient vibrations. Based on previous studies, glulam frame connections, as well as non-structural elements (external timber walls and internal plasterboard partitions) can have a significant impact on the global stiffness properties, and there is a lack of knowledge in modeling and investigation of their impact on the serviceability level building dynamics. In this paper, a numerical modeling approach with the use of "connection-zones" suitable for analyzing the taller glulam timber frame buildings serviceability level response is presented. The "connection-zones" are generalized beam and shell elements, whose geometry and properties depend on the structural elements that are being connected. By introducing "connection-zones", the stiffness in the connections can be estimated as modified stiffness with respect to the connected structural elements. This approach allows for the assessment of the impact of both glulam connection stiffness and non-structural element stiffness on the dynamic building response due to service loading. The results of ambient vibration measurements of an 18-storey glulam timber frame building, currently the tallest timber building in the world, are reported and used for validation of the developed numerical model with "connection-zones". Based on model updating, the stiffness values for glulam connections are presented and the impact of non-structural elements is assessed. The updating procedure showed that the axial stiffness of diagonal connections is the governing parameter, while the rotational stiffness of the beam connections does not have a considerable impact on the dynamic response of the glulam frame type of building. Based on modal updating, connections exhibit a semi-rigid behavior. The impact of non-structural elements on the mode shapes of the building is observed. The obtained values can serve as a practical reference for engineers in their prediction models of taller glulam timber frame buildings serviceability level response. Highlights: An alternative approach to model connections in taller glulam timber frame buildings with "connection-zones" is proposed. The impact of non-structural elements on the serviceability level response is explored. The semi-rigid behavior in glulam timber connections has been shown and estimates of the stiffness range for these connections are provided.